Experimental and numerical investigation of the effect of adding silica nanoparticles on the behavior of composite polyester resin - laleh, F.Farhang; Marzroud, A. Pourtaghi; Choupani, Naghd Ali (International Journal of Engineering and Technology, 2018)
This study examines the behavior of the composite composition of polyester resin containing silica nanoparticles and compares some of its mechanical properties, including the maximum permissible toughness and fracture toughness with the corresponding values of pure resin polyester. In other words, the present paper examines the effect of adding silica nanoparticles to polyester resins and forming a resistant nanocomposite. Silica nanoparticles are one of the important additives for polymer resins, and they promote some of their mechanical prop-erties. The experiments were carried out by the arcan device and on the butterfly arcan specimen. These specimens were loaded at seven different angles and the magnitude of maximum deflection was obtained. These angles produced pure tensile fashion, pure shear fashion, and five different modes of composite fashion, and the values of stress intensity coefficients and strain energy relaxation rates were obtained for each of the states.Â